Nexus Network Journal 12,3 Architecture and Mathematics - Williams, Kim (Nexus Network Journal, 2010)
We grasp and transform the world through interplays of quantification and qualification. The cross pollination of geometric and literary figures is deeply embedded in our cognitive habits, instruments of inquiry and the constructed environment. Through time, thought has reflected on the visible processes and products of material craft to explain and train the invisible workings of the mind. Recursively, material craft embodies a tradition of splitting ideas into categorical parts and compositional units for reassembly. Although the mathematical and verbal arts are often placed in contrast, human inventions manifest a weave of alphanumerics. Mythic parables, geometric proofs, memory arts, poems, algorithms, buildings and cities emerge from the intercourse of measure and explication. This special issue of the Nexus Network Journal considers architectonic examples of past, present and potential geometries of rhetoric.